Improving quercetin bioavailability: A systematic review and meta-analysis of human intervention studies - Liu, Lu; Barber, Elizabeth; Kellow, Nicole J.; Williamson, Gary (Food chemistry, 2025)
This systematic review evaluated a total of 31 included human intervention studies that have assessed methods to improve quercetin bioavailability from different formulations and food matrices using urine or blood samples up to July 2024. The bioavailability of quercetin in humans was affected by several factors. 1) Chemical structure: Quercetin-3-O-oligoglucosides exhibited 2-fold higher bioavailability than quercetin-3-O-glucoside, 10-fold higher than quercetin-3-O-rutinoside and ∼ 20-fold higher than quercetin aglycone. 2) Modification of physicochemical properties: In comparison to quercetin aglycone, the quercetin-3-O-glucoside-γ-cyclodextrin inclusion complex showed a 10.8-fold increase in bioavailability, while the self-emulsifying fenugreek galactomannans and lecithin encapsulation, and lecithin phytosome, showed a 62- and 20.1-fold increase, respectively. 3) Food matrix effects: the addition of dietary fats and fibre increased bioavailability by ∼2-fold. This review summarises key factors that enhance quercetin bioavailability, contributing to the development of more effective and practical quercetin supplements or functional foods for better bioactivity of quercetin in humans. •Quercetin bioavailability is increased by lipid complexation and glucosylation.•Increasing quercetin solubility and stability is not guaranteed to increase bioavailability.•Large increases in quercetin bioavailability are possible with appropriate formulation.